Pengaruh Kualitas dan Citra Merek terhadap Keputusan Pembelian iPhone pada Gen Z di Sukoharjo - Sofia Setyaningsih; Muhammad Syihabuddin (Jurnal Visi Manajemen, 2026)
This study aims to examine how Generation Z in Sukoharjo Regency makes iPhone purchases based on their impressions of the brand and product quality. Generation Z is known to be highly tech-savvy, analytical, and selective in purchasing goods, especially mobile phones. With rapid technological advancements and intense competition among smartphone brands, it is crucial for companies to understand what aspects influence young consumers' purchasing decisions. We used a quantitative approach based on survey data obtained from 30 individuals who are current iPhone users or are considering purchasing one.The decision to buy is the dependent variable in this study, whereas product quality and brand perception are the independent variables. This data analysis examines whether these two separate factors influence customer purchasing decisions. According to the study, Generation Z purchases iPhones based on brand and product quality. Based on these findings, attracting young consumers as buyers depends on positive brand perceptions and high-quality product offerings. Marketing academics, especially those specializing in consumer behavior, can benefit from the theoretical contributions of this study, while business owners and marketers can use the practical implications of this research to better target Generation Z in the digital age. Gen Z's smartphone purchases are heavily influenced by brand image and quality.